The influence of recovery duration on multiple sprint cycling performance - Glaister, M.; Stone, M. H.; Stewart, A. M.; Hughes, M.; Moir, G. L. (The Journal of Strength and Conditioning Research, 2005)
The purpose of this study was to examine the influence of recovery duration on various measures of multiple sprint cycling performance. Twenty-five physically active men completed 2 maximal multiple sprint (20 × 5 seconds) cycling tests with contrasting recovery periods (10 or 30 seconds). The mean ± SD values for age, height, and body mass were 20.6 ± 1.5 years, 177.2 ± 5.4 cm, and 78.2 ± 8.2 kg, respectively. All tests were conducted on a friction-braked cycle ergometer. Longer (30 seconds) recovery periods resulted in significantly (p < 0.05) higher measures of maximum ( 4%) and mean ( 26%) power output, the former appearing to result from a potentiation effect during the first few sprints. Thirty-second recovery periods also corresponded with significantly lower measures of fatigue (absolute difference: 16.1%; 95% likely range: 14.1-18.2%), heart rate, respiratory exchange ratio, and oxygen uptake. Blood lactate and ratings of perceived exertion (6-20 scale) increased progressively throughout both protocols and were significantly lower with 30-second recovery periods. The results of this study illustrate the considerable influence of recovery duration on various measures of multiple sprint work. Although the precise mechanisms of this response require further investigation, coaches and sport scientists should consider these findings when attempting to develop or evaluate the performance capabilities of athletes involved in multiple sprint sports.